Steel on Steel : Inside the battle for the future of Australia's biggest railroad. - Baines, Stephen (Of Queensland Rail) (University of Queensland Press, 2014)
The inside story of the privatisation of the freight arm of Queensland Rail and one of the most extraordinary transformations of a company in the history of Australian business. An icon that touched every part of life in the state, Queensland Rail (QR) was famously and audaciously catapulted into the private sector in 2010 after more than 140 years of government ownership. CEO Lance Hockridge and state Treasurer Andrew Fraser oversaw the privatisation, which simultaneously involved a massive de-merger from the passenger rail business and a 4. billion initial public offering all executed.